Gender has no influence on VUR rates after renal transplantation. (November 2014) - Farr, Alex; Györi, Georg; Mühlbacher, Ferdinand; Husslein, Peter; Böhmig, Georg A.; Margreiter, Markus
Summary The influence of recipient gender on urological complications including vesicoureteral reflux (VUR) after renal transplantation has not yet been established. In this study, post‐transplantation voiding cystourethrography and ultrasonography were used to evaluate the upper and lower urinary tract in 598 consecutive renal transplant recipients. Our cohort included 209 females and 389 males, respectively. Gender‐specific urological complications and potential confounders were analyzed in relation to long‐term allograft outcomes. Postoperative urinary retention occurred more frequently in men (P = 0.004). Urinary tract infections (UTIs) were diagnosed more frequently in women after transplantation (P = 0.05). In a multivariate analysis, gender was not a risk factor for VUR [HR, 1.35 (CI, 0.90–1.96); P = 0.14]. VUR rates were influenced by the surgeon's experience level at the time of transplantation [HR, 0.59 (CI, 0.40–0.87); P = 0.008]. No gender‐specific differences were seen for ureteral stenosis, leakage, hydronephrosis, death‐censored graft or patient survival, and long‐term allograft function. Donor/recipient gender mismatch had no impact on postoperative complication rates. In conclusion, male transplant recipients are at risk for developing postoperative urinary retention, whereas female patients more likely develop UTIs. Surgeon's experience level is a risk factor for developing VUR.